EFFECTIVENESS OF ONLINE LEARNING IN HOSPITALITY AND TOURISM MANAGEMENT STUDY PROGRAM AT RUNATA BUSINESS COLLEGE - Elsita Lisnawati Guntar; A.A. Istri Ngurah Dyah Prami; Joana Josevira L. Ketaren (Lembaga Pengembangan Pembelajaran Penelitian dan Pengabdian Masyarakat Universitas PGRI Mahadewa Indonesia, 2023)
This research aims to find out the effectiveness of online learning in the Hospitality and Tourism Management Study Program at Runata Business College. This research is descriptive analysis study by using a quantitative approach. The data were collected by using questionnaires, interviews, observation, and documentation methods. The number of samples used in this study was 30 students who were determined based on the census sample method. The validity test in this study used Alpha Cronbach, while data analysis used simple linear regression. The results of this study found that effectiveness had a positive and significant effect on online learning, with a value of 0.029<0.050 which identifying that H0 was rejected and H1 was accepted.